MODERN CONCEPTS AND ARCHETYPES OF THE MANAGEMENT IN EDUCATION: PSYCHOLOGICAL, SOCIAL AND ECONOMICAL ASPECTS - Arpentieva M.R.; Gasanova R.R.; Gorelova I.V.; Kamenskaya E.N.; Kassymova G.K.; Kosov A.V.; Kraynova E.R.; Lavrinenko S.V. (Scientific Journal of Pedagogy and Economics, 2020)
The purpose of this study is to study modern conceptual management in education. The conceptual management of education in general and of individual educational institutions, in contrast to contextual management, allows and requires to highlight its elements, functional capabilities and, most importantly, clearly define the subject and object. Existing management concepts are eclectically presented in the Russian discourse and practices of managing education and other areas of social activity. The system of professional standards developed in the country is designed to solve a number of managerial tasks. However, the non-conceptual use of professional standards brings more harm than good in the field of culture and education, as well as in other areas. Failure to comply with professional standards leads to de-professionalization and the destruction of education management and education itself. The latter is illustrated by the text of regional strategies: as a rule, they do not have clearly articulated ideas about the development of education, and there are no concrete ideas about the development of regions and the country as a whole. Thus, such pseudo-strategies act as a brake on the development of education, and can also serve its destruction. The presence of management strategies based on a conceptual approach in the management of education is an incentive for development. However, the lack of an algorithm for compiling and evaluating documents on the development strategy of a country, region, and education in a country and region makes it impossible to recognize the importance of this aspect in the functioning and development of the state, business, community, and violations in the field of culture and education. Such violations lead to deformations in the process of evaluating the activities of educational authorities and “authorities” in the region as a whole. This leads to the fact that this strategic management remains unclaimed in the system of territorial, local (self) management.